The congruence of theoretical and empirical patterns of inter-store price competition - Daniel Klapper; Lee G. Cooper; Lutz Hildebrandt (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
The present paper concentrates on the nature and structure of inter-store price competition. It focusses especially on price competition between different retailers within one trading area and within one product category. Six theoretically founded hypotheses postulate competitive relations between manufacturers' UPCs and the retailers covering various possible competitive conditions such as competitive independencies or various degrees of competitive dependency among the UPCs and the retailers. These hypotheses have been tested empirically with store-level scanner data. UPC is the Universal Product Code, the most dominant coding technology in the United States. It allows for point-of-sale (POS) scanning systems and to continuously collect data by item at the retail level. The retail prices of 27 UPCs from a five stores suburban market place measured over 104 weeks are analyzed by using the three-mode component analysis to determine the basic and important competitive conditions in the market under study. On the basis of the estimated component structure of the UPCs, of the stores and of the weeks as well as on the basis of the core array, which provides the information of how the components of different modes (here UPCs, stores, and weeks) are related to each other the appropriateness of the six research hypotheses is tested. The empirical results support the theoretical implications that the price competition between UPCs and retailers in one product category and one trading area is primarily determined by manufacturers' pricing strategies. The manufacturer set the retail prices (shelf prices and temporary price reductions) by deciding on the number and size of the trade deals whereas the retailers exert passive pricing strategies by passing some or most of the trade deals through to their consumers.
urn:nbn:de:kobv:11-10046317
Keywords: 330; Pricing Research; Game Theory; Price Competition among Manufacturers and Retailers; Empirical Industrial Organization